   ### 5.15.2  Transform an expression into a function : unapply

unapply is used to transform an expression into a function.
unapply takes two arguments an expression and the name of a variable.
unapply returns the function defined by this expression and this variable.

Warning when a function is defined, the right member of the assignment is not evaluated, hence `g:=sin(x+1); f(x):=g` does not defined the function f: x → sin(x+1) but defines the function f: xg. To defined the former function, unapply should be used, like in the following example:
Input :

g:= sin(x+1); f:=unapply(g,x)

Output :

(sin(x+1), (x)->sin(x+1))

hence, the variable g is assigned to a symbolic expression and the variable f is assigned to a function.
Input :

unapply(exp(x+2),x)

Output :

(x)->exp(x+2)

Input :

f:=unapply(lagrange([1,2,3],[4,8,12]),x)

Output :

(x)->4+4*(x-1)

Input :

f:=unapply(integrate(log(t),t,1,x),x)

Output :

(x)->x*log(x)-x+1

Input :

f:=unapply(integrate(log(t),t,1,x),x)
f(x)

Output :

x*log(x)-x+1

Remark Suppose that f is a function of 2 variables f:(x,w)→ f(x,w), and that g is the function defined by g: whw where hw is the function defined by hw(x)=f(x,w).
unapply is also used to define g with Xcas.
Input :

f(x,w):=2*x+w
g(w):=unapply(f(x,w),x)
g(3)

Output :

x->2·x+3   